Repellents against Aedes aegypti bites: synthetic and natural origins - Noguera-Gahona, Melissa; Peña-Moreno, Cindy; Quiñones-Sobarzo, Natalia; Weinstein-Oppenheimer, Caroline; Guerra-Zúñiga, María; Collao-Ferrada, Ximena (Frontiers in Insect Science, 2025)
Dengue fever, transmitted by mosquitoes of the Aedes genus, particularly Aedes aegypti, has emerged as a global health issue. With the expansion of this mosquito to new geographical areas, driven by factors such as climate change, the need for preventive measures like using insect repellents has become critical. The present review explores the current state of the art on topical mosquito repellents, both synthetic and natural, used globally, especially in regions where dengue is endemic. Among synthetic repellents, DEET is the most widely used, supported by investigations demonstrating its efficacy and safety, although concerns about its toxicity exist in exceptional cases. Other compounds, such as picaridin, IR3535, and PMD are also common and offer alternatives with variable safety and efficacy profiles. Natural repellents, such as essential oils of citronella, lemon eucalyptus, and clove, have proven effective against Aedes aegypti. However, they present challenges due to rapid volatilization and the limited duration of their protective effect. To address these issues, combinations of essential oils and synthetic compounds have been proposed to improve efficacy and safety. Finally, the review highlights the complexity and the challenges of developing new repellents, including the high costs and lengthy timelines for commercialization, as well as the importance of continued research to improve the efficacy and safety of these products.